2014
DOI: 10.3846/16486897.2014.937438
|View full text |Cite
|
Sign up to set email alerts
|

Flood Pattern Changes in the Rivers of the Baltic Countries

Abstract: Estimation of both the frequency and variation of spring floods is a key issue for the assessment and management of flood risks. Changes in river floods in Estonia, Latvia and Lithuania have been investigated in few national studies. However, there are no studies of the changes of flood patterns by using a common methodology for the rivers of this region. In this study flood pattern changes in the rivers of the Baltic countries were estimated applying trend and frequency analysis for the periods of 1922–2010, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…In the Continental region, Villarini et al (2011) 1922, 1941and 1961(Reihan et al, 2012, as well as in the period 1922-2010 (Sarauskiene et al, 2015). These findings are in agreement with the decreasing trends found in the Lithuanian gauging station in the periods 1900-1999 and 1920-1999. In the Scandinavian region, Wilson et al (2010) analysed trends in both the timing and magnitude of floods over three periods (1920-2005, 1941-2005, 1961-2000) in the Nordic countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the Continental region, Villarini et al (2011) 1922, 1941and 1961(Reihan et al, 2012, as well as in the period 1922-2010 (Sarauskiene et al, 2015). These findings are in agreement with the decreasing trends found in the Lithuanian gauging station in the periods 1900-1999 and 1920-1999. In the Scandinavian region, Wilson et al (2010) analysed trends in both the timing and magnitude of floods over three periods (1920-2005, 1941-2005, 1961-2000) in the Nordic countries.…”
Section: Discussionsupporting
confidence: 88%
“…This applies both in terms of enlarging available datasets in time and space and a better consideration of large-scale climatic drivers (Kjeldsen, 2011;Hall et al, 2014). Examples of recent studies that consider changes in flood records at larger and transnational scales include the Nordic countries (Wilson et al, 2010), Central Europe (Villarini et al, 2011), the Baltic States (Reihan et al, 2012;Sarauskiene et al, 2015) and North America (Hodgkins and Dudley, 2006;Vogel et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The importance of the 1989 RS has been previously shown for specific elements of the regional climate system including the detection of shifts in atmospheric circulation [43], meteorological regime [45], severity of winters [54], precipitation [45], seasonal river runoff [55, 56], cumulative wind stress [57], sea level and maximum ice cover [54]. These studies did not, however, inform us of the magnitude of RSs in the climate system and the degree to which the processes are reversible.…”
Section: Discussionmentioning
confidence: 99%
“…The summing up of the ranks revealed that the GEV is the most suitable distribution for flood‐frequency analysis. The analysis of changes in flood patterns in the Baltic countries disclosed that the distribution of GEV represents the most valid model for extreme events of the analysed rivers (Sarauskiene et al ., ). However, a study carried out in England (Esteves, ) demonstrated that the distribution of GEV does not always provide the best‐fitting data for the analysis of extreme rainfall.…”
Section: Discussionmentioning
confidence: 97%